The Travails of Identity Change: Competitor Claims and Distinctiveness of British Political Parties, 1970–1992 - Karthikeyan, Soorjith Illickal; Jonsson, Stefan; Wezel, Filippo Carlo (Organization Science, 2016)
How does an organization change its identity, yet maintain distinctiveness? This question is especially interesting when we consider the fact that identity repositioning often takes place among several organizations at the same time—giving rise to interrelated identity change and distinctiveness concerns. We investigate this question in the setting of British political parties, during a period when questions of identity change and distinctiveness were heightened, following a decline of political ideologies. Parties, we argue, sought to handle this situation through two broad strategies that we call identity affirmation and reformation. Identity distinctiveness was affirmed by identity claims that sought to counter and neutralize competing claims on aspects that were thought central to the identity of the party. To alter the identity, parties also sought to reform it by expanding identity claims to elements that were considered to be popular. Reformation efforts are however not unchecked expansion, but tempered by concerns of identity consistency and distance from other parties. We discuss contributions to theories of organizational identities and competitive rivalry.